FROM ADMINISTRATIVE TO STRATEGIC: THE EVOLUTION OF THE HR FUNCTION - Firdaus; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This paper synthesizes existing literature to trace and analyze the evolution of the Human Resources function from its administrative origins to its contemporary role as a strategic partner. It delineates the historical stages of this transformation, highlighting the paradigm shift from viewing employees as a cost to be controlled to recognizing them as human capital to be invested in. The paper identifies technology, changing business models, and academic thought as the primary enablers of this change. It also examines the persistent barriers—such as perceptual legacies and critical skill gaps—that hinder this evolution. The conclusion underscores that for HR to be an indispensable driver of competitive advantage, it must fully embrace its strategic potential, requiring a continuous redefinition of its competencies and value proposition.